ANALYSIS OF EXHAUST EMISSIONS, NOISE, AND PERFORMANCE OF A 110CC MOTORCYCLE USING A PERFORATED-CLOSE CONICAL SILENCER MUFFLER - khoirul huda; Kriswanto; Abdurrahman; MUHAMMAD NUR FAIZIN; Khoirudin Fathoni; Atta Putra Harjanto; R. Imanu Danar Herunandi; R. Ambar Kuntoro Mursit Gendroyono; Nugroho Fajar Susanto (Jurnal Pendidikan Teknik Mesin, 2025)
This paper analyzes the exhaust emission, noise, and performance of 110cc motorcycles experimentally through PCCS exhausts compared to standard exhausts. This study adopts an experimental method involving three tests: exhaust emission testing based on the SNI 09-7118.1-2005 standard, noise measurement using the static test procedure according to the UN-R 41-04 standard, and performance evaluation conducted with an inertial dynamometer. Implementing the PCCS exhaust system on a 110 cc automatic motorcycle positively impacts exhaust emissions, noise levels, and engine performance. Compared to the standard exhaust, the PCCS significantly reduces CO and HC emissions by 78.99% and 55.99%, respectively, while maintaining noise levels within regulatory limits in urban conditions. In terms of performance, the PCCS delivers higher torque and power output, particularly in the 3500–5500 RPM range, which aligns with typical riding conditions. These improvements are attributed to the system’s efficient exhaust flow and reduced backpressure. The PCCS exhaust presents a promising solution for enhancing environmental sustainability, performance, and rider comfort in small-displacement motorcycles.